Wild chimpanzees are infected by Trypanosoma brucei - Jirků, Milan; Votýpka, Jan; Petrželková, Klára J.; Jirků-Pomajbíková, Kateřina; Kriegová, Eva; Vodička, Roman; Lankester, Felix; Leendertz, Siv Aina J.; Wittig, Roman M.; Boesch, Christophe; Modrý, David; Ayala, Francisco J.; et al. (Elsevier Science BV, 2015)
sickness, very little is known about their trypanosome infections, mainly due to major difficulties in obtaining their blood samples. In present work, we established a diagnostic ITS1-based PCR assay that allows detection of the DNA of all four Trypanosoma brucei subspecies (Trypanosoma brucei brucei, Trypanosoma brucei rhodesiense, Trypanosoma brucei gambiense, and Trypanosoma brucei evansi) in feces of experimentally infected mice. Next, using this assay we revealed the presence of trypanosomes in the fecal samples of wild chimpanzees and this finding was further supported by results obtained using a set of primate tissue samples. Phylogenetic analysis of the ITS1 region showed that the majority of obtained sequences fell into the robust T. brucei group, providing strong evidence that these infections were caused by T. b. rhodesiense and/or T. b. gambiense. The optimized technique of trypanosome detection in feces will improve our knowledge about the epidemiology of trypanosomes in primates and possibly also other endangered mammals, from which blood and tissue samples cannot be obtained. Finally, we demonstrated that the mandrill serum was able to efficiently lyse T. b. brucei and T. b. rhodesiense, and to some extent T. b. gambiense, while the chimpanzee serum failed to lyse any of these subspecies.
Keywords: Trypanosomes; Chimpanzee; Non-human primates; Transmission; Diagnostics